New study of geometry effect on chiral metamateri-al nanostructures - Mezache, Zinelabiddine; Zara, Chemseddine; Larioui, Fateh; Benabdelaziz, Fatiha (International Journal of Physical Research, 2017)
In this paper, the Comsol Multiphysics version 5.0 is used to study the effect of geometric parameters on transmission of chiral metamaterial nanostructures. The angle of the chiral metamaterial element was varied to see his effect. Transmission coefficient (S21) and reflection coefficient (S11) are computed. In the case of nano chiral metamaterial structure, and depending on the application, the electromagnetic behavior can be adjusted by changing the angle of the chiral element.